Cynicism as Mediation The Effect of Career Plateau and Burnout on Turnover Intention - Rico Edi Saputro; Ryan Basith Fasih Khan (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2026)
The growing turnover of healthcare staff is a major concern for healthcare organizations because it affects employment stability and service quality. Factors such as career stagnation and chronic fatigue are intricately linked to turnover intention; however, cynicism may influence this relationship by either reinforcing or diminishing it. This research seeks to assess the relationship between career plateau and burnout, with cynicism as a mediating variable, on turnover intention among healthcare workers in East Java. This research employed a quantitative methodology utilizing an explanatory design. The research sample included 122 respondents who were chosen by purposive sampling. The research instrument used was a Likert scale questionnaire, which was analysed using SmartPLS 3. The findings of the research indicated that career stagnation significantly influenced turnover intention, alongside chronic fatigue. Furthermore, cynicism exhibited a partial correlation with both career stagnation and burnout. This indicates that healthcare organisations ought to focus on career development and burnout prevention to mitigate employee turnover rates.